2015
DOI: 10.1080/00405000.2015.1049069
|View full text |Cite
|
Sign up to set email alerts
|

A novel plied yarn structure with negative Poisson’s ratio

Abstract: This article presents an experimental and geometrical study of a novel kind of plied yarn structure with negative Poisson's ratio (NPR). The deformation mechanism of the yarn structure formed with two stiff yarns and two soft yarns to achieve NPR behavior was firstly introduced. Based on the proposed yarn structure, four kinds of yarn samples were then fabricated with two kinds of stiff yarns and two types of soft yarns and tested under the axial extension to verify their auxetic or NPR effect. A geometric ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 30 publications
0
67
1
Order By: Relevance
“…In this review we refer to this yarn as the DHY. Development of the DHY includes an auxetic plied yarn [212], auxetic braided structure [160], and a DHY where the 'wrap' fibre is stitched in place to offer more control over its behaviour by preventing fibre slippage [213]. Heat treatment has also been utilised to solve the issue of slippage [214].…”
Section: Fabricating Auxetic Textilesmentioning
confidence: 99%
“…In this review we refer to this yarn as the DHY. Development of the DHY includes an auxetic plied yarn [212], auxetic braided structure [160], and a DHY where the 'wrap' fibre is stitched in place to offer more control over its behaviour by preventing fibre slippage [213]. Heat treatment has also been utilised to solve the issue of slippage [214].…”
Section: Fabricating Auxetic Textilesmentioning
confidence: 99%
“…Studies of HAY were predominantly focused on DHY, until recently, Ge et al has developed a new approach to produce negative Poisson's ratio in yarn with a specific 4‐ply structure . The work of Ge et al included a geometric analysis to calculate the Poisson's ratio values of the auxetic plied yarn for any given tensile strain, and the experimental result revealed that the geometrical model was only capable of predicting the Poisson's ratio at high strains.…”
Section: Introductionmentioning
confidence: 99%
“…These properties include shear modulus, energy absorbance, vibration damping, [5][6][7][8][9] sound absorption, [10] indentation resistance, [11][12][13] and synclastic behavior for better formability. [14] The known naturally and manmade auxetic materials include metals, [15] laminates, [16] gels, [17] crystalline structures, [18][19][20] polymers, [21,22] composites, [6,8,23] foams, [1,24] and textile materials including fibers, [22,25] yarns, [26][27][28][29][30] and fabrics including woven fabrics, [26,27,[31][32][33][34][35][36][37] weft-knitted fabrics, [38][39][40][41][42][43] warp-knitted fabrics, [44][45][46]…”
Section: Introductionmentioning
confidence: 99%